2004
DOI: 10.1902/jop.2004.75.9.1281
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Periodontal Tissue Regeneration by Transplantation of Bone Marrow Mesenchymal Stem Cells

Abstract: These findings suggest that auto-transplantation of bone marrow mesenchymal stem cells is a novel option for periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
230
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(235 citation statements)
references
References 51 publications
3
230
0
2
Order By: Relevance
“…MSCs may have been the primary contributing factor as they offered a source of cells that were ready to regenerate. 14,41,42 There is dynamic secretion of transduced BMP-2 protein in vivo and the concentration of local BMP-2 may be affected by the niche. The ex vivo culture may be controlled by the total fluid amount, CO 2 and O 2 conditions without any other protein interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs may have been the primary contributing factor as they offered a source of cells that were ready to regenerate. 14,41,42 There is dynamic secretion of transduced BMP-2 protein in vivo and the concentration of local BMP-2 may be affected by the niche. The ex vivo culture may be controlled by the total fluid amount, CO 2 and O 2 conditions without any other protein interference.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Periodontal regeneration therapy with transplanted MSCs has been shown to increase the regeneration of the cementum, periodontal ligaments and alveolar bone. 14 In a previous study, MSCs were induced into an osteogenic phenotype, such that they were able to repair alveolar bone defects (5-mm high) without investigating the periodontal attachment apparatus. 15 Previously, we reported that replication-defective adenoviral BMP-2 gene transfer to MSCs increased bone formation in critical-sized craniofacial bony defects.…”
Section: Introductionmentioning
confidence: 99%
“…They have been incorporated in class III furcation defects in canine models resulting in successful results [47]. BMMSCs were present in the defect even after 1 month, suggesting that they ultimately form various periodontal cells needed for regeneration [47].…”
Section: Bone Marrow Derived Mesenchymal Stem Cells (Bmmsc)mentioning
confidence: 99%
“…Thus, the bone marrow provides an alternative source of MSC for the treatment of periodontal diseases. 15 Bone marrow-derived MSC share numerous characteristics with dental pulp stem cells (DPSC) and are both able to form bone-like or tooth-like structures. However, BMSC display a lower odontogenic potential than DPSC, indicating that MSCs from different embryonic origins are not equivalent.…”
Section: Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%